Pain intensity, neck pain and longer duration of complaints predict poorer outcome in patients with shoulder pain – a systematic review. Issue 1 (December 2015) - Kooijman, Margit; Barten, Di-Janne; Swinkels, Ilse; Kuijpers, Ton; de Bakker, Dinny; Koes, Bart; Veenhof, Cindy
Abstract Background Shoulder complaints are common and have an unfavourable prognosis in many patients. Prognostic information is helpful for both patients and clinicians in managing the complaints. The research question was which factors have prognostic value on (un)favourable outcome in patients with shoulder complaints in primary care, secondary care and occupational settings. Methods Update of a systematic review in primary care, secondary care and occupational settings. Results Nine articles were published since the original review in 2004. Six were of high quality covering a wide variety of prognostic factors and outcome measures. Four studies were conducted in primary care settings. A best evidence synthesis, including the results of the previous systematic review on this topic shows that there is strong evidence that higher shoulder pain intensity, concomitant neck pain and a longer duration of symptoms predict poorer outcome in primary care settings. In secondary care populations, strong evidence was found for the association between greater disability and poorer outcome and between the existence of previous shoulder pain and poorer outcome. Conclusion Clinicians may take these factors into account in the management of their patients. Those with a worse prognosis may be monitored more frequently and the treatment plan modified if complaints persist.